Adsorption Of Chemically Prepared Cocoa Nibs Based Activated Carbon Onto Methylene Blue: Equilibrium And Kinetic Studies - KhairulAdli Nikman; Fisal Ahmad; MohdSukri Hassan; Khairunisa Nikman; Mohd Azmier Ahmad (Madridge Publishers, 2024)
Non-Indexed Publication